Pengaruh Kompetensi Karyawan, Motivasi Intrinsik dan Kecerdasan Emosional Terhadap Kinerja : (Studi Pada Karyawan Burger King Semarang) - Ranti Suryani; Hawik Ervina Indiworo; Ika Indriasari (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This research aims to analyze the influence of competence, intrinsic motivation and emotional intelligence on the performance of Burger King Semarang employees. The method used was quantitative with a sample of 109 respondents using purposive sampling technique. Data analysis includes descriptive analysis of variables, classical assumption tests (normality, heteroscedasticity and multicollinearity), multiple linear regression analysis, as well as t tests, f tests and coefficient of determination tests. The research results show: (1) The t test shows that competence (tcount = 0.002 > ttable 0.05) and emotional intelligence (tcount = 0.000 < ttable 0.05) have a positive and significant effect on employee performance. (2) The F test shows the value of Fcount = 0.000 < Ftable = 0.05, indicating that simultaneously competence, intrinsic motivation and emotional intelligence have a significant effect on employee performance. (3) The coefficient of determination (R² = 0.979) shows that 97.9% of the variation in employee performance can be explained by the variables of competence, intrinsic motivation and emotional intelligence, while the remaining 2.1% is influenced by other variables such as work experience, incentives and promotions. position.